ICT procurement officer competency measurement model for Malaysia public sector / Azran Ahmad - Ahmad, Azran (2021)
The designation of Procument Office (PO) is temporary appointed for Malaysia public sector procurement procedure. PO is significantly involved in evaluating and recommending potential vendors to implement the public sector Information and Communication Technology (ICT) project. However, based on the recent report, there are still projects experience several issues caused by deficiency of appointed vendor. Furthermore, the study has found that the absent of competency measurement mechanisme has left the appointment of PO was based on officer’s current positions in organization rather than based on competency merit. This situation is believed contributed to the PO inefficiency in choosing the right vendor that influenced the success of the project implementation. Based on this circumstance, the study is aim to construct a competency measurement model, specifically to yield the competency profile of public officers in upholding their tasks as PO by using a set of self-assessment questionnaire based on model developed. The competency profile expected to serve as a mechanism for consideration in appointment of PO for ICT Technical Evaluation Committee in ICT Procurement Procedure in Malaysia Public Sector. The method applied by this study is a mixed-method approach performed by quantitative – survey-questionnaire as the dominant approach and qualitative – interview session as the minor approach. The primary analysis for the main data is Rasch Measurement Model. There were four (4) main activities involved; i. Systematic Literature Review to develop a conceptual model, ii. Face Validity and Reliability Test for competency attributes and instrument establishment, iii. Pilot Test for instrument’s validation and verification, and iv. Competency Profiling to describe the identity of officer competency level. The study has concluded the PO Competency Measurement Model is efficient to identify the level of PO competency according to credential possessed by the officer for PO appointment consideration. This model expected to be considered as one of the procedure in the management of ICT procurement in Malaysia public sector. In future, it is recommended for the model to explore on measurement of competency for Malaysia public servant in different job scope or designation. This model also anticipates on further discussion of PMBOK with the concern on competency measurement mechanism establishment.